Saúde física do Tradutor e Intérprete de Libras na esfera educacional - Silva, Ana Luiza dos Santos (Universidade Federal de São Carlos, 2023)
This work aimed to investigate the physical health of Brazilian Sign Language (Libras)/Portuguese Language Translators and Interpreters (TILS) who work in schools. It was intended to problematize the working conditions and possible health problems that may be presented by these professionals as a result of their working conditions. This is a qualitative and exploratory research, in which online questionnaires were applied to TILS professionals in the State of São Paulo, who worked in Elementary School or had worked in the last two years. Ten professionals participated in the study. The questionnaire had objective and essay questions that dealt with the physical health and working conditions of professionals. Data analysis was carried out according to the laws that guides the work of TILS and of studies that deal with the physical health of Brazilian Sign Language (Libras)/Portuguese Language Translators and Interpreters (TILS) who work in the school environment. The results indicate different factors that can lead TILS to develop diseases such as repetitive strain injury work- related muculoskeletal disorders (WRMD) due to repetitive movements.
Physical health of Libras translator and interpreter in the educacional sphere
Keywords: Tradutor intérprete de Libras; Saúde física; Trabalho; CIENCIAS HUMANAS